The farm, the city, and the emergence of social security - Elizabeth M. Caucutt; Thomas F. Cooley; Nezih Guner (Institute for the Study of Labor (IZA), 2008)
In this paper we study the social, demographic and economic origins of social security. The data for the U.S. and for a cross section of countries make it clear that urbanization and industrialization are strongly associated with the rise of social insurance. We describe a model economy in which demographics, technology, and social security are linked together. We study an economy with two locations (sectors), the farm (agricultural) and the city (industrial). The decision to migrate from rural to urban locations is endogenous and linked to productivity differences between the two locations and survival probabilities. Furthermore, the level of social security is determined by majority voting. We show that a calibrated version of this economy is consistent with the historical transformation in the United States. Initially a majority of voters live on the farm and do not want to implement social security. Once a majority of the voters move to the city, the median voter prefers a positive social security tax. In the model social security emerges and is sustained over time as a political and economic equilibrium. Modeling the political economy of social security within a model of structural change leads to a rich economic environment in which the median voter is identified by both age and location.
urn:nbn:de:101:1-20081014362
Keywords: H55; 330; Social security; political economy; structural change; migration; Bevölkerungsentwicklung; Strukturwandel; Sozialversicherung; Landwirtschaft; Industrie; Wirtschaftsmodell; Wirtschaftsgeschichte; USA